Perbandingan Ekstrakurikuler di Sekolah Swasta dan Negeri Berdasarkan Hasil Observasi - Dianisa Wahyuni; Rika Hanipah; Zaskia Putri Aulia Azzahra; Agus Mulyana (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2024)
This article discusses the differences in extracurricular activities between private and public schools in Indonesia. Private schools, supported by greater financial resources, offer a variety of activities with modern facilities. On the other hand, public schools, despite their limited budgets, still ensure equal access to education. Comparisons include infrastructure, fees, student numbers and extracurricular opportunities. Factors such as gender, religion and culture influence the offering of activities. Qualitative research methods and observations were used to explain the differences in planning, types of activities and assessment between the two. Field observations highlighted barriers in private and public schools, including facilities constraints. This article examines the strengths and weaknesses of the two schools observed, providing a holistic insight into the impact of educational institutions on student character building in Indonesia.